2018
DOI: 10.1038/s41598-018-25139-8
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of multidrug and toxin extrusion protein 1 (MATE1) to renal secretion of trimethylamine-N-oxide (TMAO)

Abstract: Trimethylamine-N-oxide (TMAO) gained considerable attention because of its role as a cardiovascular risk biomarker. Organic cation transporter 2 (OCT2) mediates TMAO uptake into renal proximal tubular cells. Here we investigated the potential role of multidrug and toxin extrusion protein 1 (MATE1) for translocation of TMAO across the luminal membrane of proximal tubular cells. HEK293 cells stably expressing OCT2 (HEK-OCT2) or MATE1 (HEK-MATE1) were used for uptake studies. Transcellular transport of TMAO was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 44 publications
(89 reference statements)
1
23
0
Order By: Relevance
“…Yet, we did not find a significant correlation between plasma levels of TMAO and total protein intake. Moreover, several studies in animal or cellular models have shown involvement of tubular transporters such as organic cation transporter 2 (OCT2) in TMAO cellular uptake and efflux [23,24,25]. This, however, has not been confirmed in humans unlike what has been previously described for creatinine [25].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, we did not find a significant correlation between plasma levels of TMAO and total protein intake. Moreover, several studies in animal or cellular models have shown involvement of tubular transporters such as organic cation transporter 2 (OCT2) in TMAO cellular uptake and efflux [23,24,25]. This, however, has not been confirmed in humans unlike what has been previously described for creatinine [25].…”
Section: Discussionmentioning
confidence: 99%
“…TMAO is eventually cleared mainly by the kidneys, excreted in urine in part through tubular cell secretion involving uptake by organic cation transporters (OCTs) OCT1 and OCT2 as well as transporters of the ATP-binding cassette (ABC) family, including ABCG2 (BCRP) and ABCB1 (MDR1) [ 71 , 72 ]. Multidrug and toxin extrusion protein 1 (MATE1) contributes to translocation of TMAO across the luminal membrane of proximal tubular cells [ 73 ]. Indeed, genetic ABCG2 variants modulate TMAO exposure in humans [ 72 ].…”
Section: Metabolite Overload: Microbiota-generated Nephrotoxinsmentioning
confidence: 99%
“…In healthy subjects, TMAO is efficiently excreted in the urine to maintain serum levels below about 10 μM [ 60 , 71 , 129 , 138 ]. Glomerular filtration and uptake by proximal tubular cells through organic cation transport proteins regulates circulating TMAO and prevents excess accumulation [ 133 , 139 , 140 ]. While small amounts may be secreted as TMA after retroconversion, renal FMO3 and 1 expression accounts for over 96% being excreted as TMAO [ 128 , 129 , 141 , 142 ].…”
Section: Tmao Accumulation In Serummentioning
confidence: 99%